Utility of immature granulocyte count in differentiating between pyelonephritis and cystitis in pediatric patients - NARSAT, Mehmet Ali; GÜLTEN, Sedat; YILDIZ, Eren (Journal of Health Sciences and Medicine, 2023)
Aims: Immature granulocyte (IG) is an easily accessible and inexpensive test that can be measured in hemogram parameters without additional analysis. It can be used in differentiation because of its practical applicability. This study aimed to investigate the role of IG count and inflammation-related complete blood count (CBC) parameters in differentiating between cystitis (CYS) and pyelonephritis (PYL) in pediatric patients. Methods: This retrospective cross-sectional study analyzed data from 79 pediatric patients (40 with PYL and 39 with CYS) who presented at a hospital pediatric outpatient clinic between January 2020 - February 2021. In addition to clinical symptoms and signs, laboratory and urinalysis results were evaluated. Laboratory analyses focused on IG count, IG percentage, and all hemogram parameters. Results: No significant demographic differences were observed between the PYL and CYS groups (p>0.05). IG counts, and C-reactive protein levels significantly differed between the two conditions (p
Keywords: Pediatric Surgery; Immature granulocyte; C-reactive protein; pyelonephritis; cystitis; Çocuk Cerrahisi; 3. Good health